Influence of Technological Environment on Performance of Gated Community Housing Projects in Nairobi County, Kenya - Musyoka, Michael Chris; Gakuu, Christopher; Kyalo, Dorothy Ndunge (European Scientific Journal, ESJ, 2017)
The principal objective of the study reported in this article was to empirically assess the influence of technological environment on performance of gated community housing projects in Nairobi County, Kenya. The study population comprised of all active gated community housing projects initiated in 2009 â€“ 2014. A total of 572 respondents were drawn from 143 sampled gated community housing projects from the seventeen sub-counties of Nairobi County (four members were drawn from each sampled gated community project â€“ client, consultant, contractor, and the gated community facility manager) using census, stratified, simple random, and purposive sampling techniques. A standardized open ended interview guide and a questionnaire with both open and closed-ended items with Likert-type interval scale anchored on a five point scale were used to collect data. Descriptive statistics show that respondents agreed that to a very great extent their projects used locally made plant and equipment (M=4.80, SD=0.40), to a great extent skills were available for operation of the plant and equipment (M=4.04, SD=0.47), to a great extent team members with necessary skills to operate and use the plant equipment were available (M=4.0, SD=0.43), to a very great extent use of information and communication technology (ICT) was satisfactory (M=4.49, SD=0.71), to a very great extent computer aided drafting (CAD) was used (M=4.62, SD=0.71), to a very great extend 3D visual illustrations - Building Information Modelling, was used (M=4.65, SD=0.48), and to a very greatÂ extent electronic mails and communication was used (M=4.86, SD=0.34. Results from inferential statistics show that r is equal to 0.559, indicating that technological environment has a moderately strong influence on performance in gated community housing projects. The value of r squared is 0.312, indicating that technological environment explains 31.2% of the variation in the performance in gated community housing projects in Nairobi County, Kenya. The Î² coefficient is 0.327, indicating that technology environment had statistically significant influence on the performance of gated community housing projects (Î²=0.327, t= 4.758, p=0.000<0.05). Considering the p value, it can be noted that the p value for technological environment (p=0.000) is statistically significant. The Î² value imply that one unit change in performance in gated community housing project is associated with 32.7% changes in technological environment.